If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (w + 9)(w + -15) = 0 Reorder the terms: (9 + w)(w + -15) = 0 Reorder the terms: (9 + w)(-15 + w) = 0 Multiply (9 + w) * (-15 + w) (9(-15 + w) + w(-15 + w)) = 0 ((-15 * 9 + w * 9) + w(-15 + w)) = 0 ((-135 + 9w) + w(-15 + w)) = 0 (-135 + 9w + (-15 * w + w * w)) = 0 (-135 + 9w + (-15w + w2)) = 0 Combine like terms: 9w + -15w = -6w (-135 + -6w + w2) = 0 Solving -135 + -6w + w2 = 0 Solving for variable 'w'. Factor a trinomial. (-9 + -1w)(15 + -1w) = 0Subproblem 1
Set the factor '(-9 + -1w)' equal to zero and attempt to solve: Simplifying -9 + -1w = 0 Solving -9 + -1w = 0 Move all terms containing w to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -1w = 0 + 9 Combine like terms: -9 + 9 = 0 0 + -1w = 0 + 9 -1w = 0 + 9 Combine like terms: 0 + 9 = 9 -1w = 9 Divide each side by '-1'. w = -9 Simplifying w = -9Subproblem 2
Set the factor '(15 + -1w)' equal to zero and attempt to solve: Simplifying 15 + -1w = 0 Solving 15 + -1w = 0 Move all terms containing w to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + -1w = 0 + -15 Combine like terms: 15 + -15 = 0 0 + -1w = 0 + -15 -1w = 0 + -15 Combine like terms: 0 + -15 = -15 -1w = -15 Divide each side by '-1'. w = 15 Simplifying w = 15Solution
w = {-9, 15}
| 13xy+18xy-20xy= | | 65=.2(w-10)4 | | 1+5y=8x-20 | | 4x+6x-17=2(2x+3x) | | -y+124=30 | | 9a+2=20 | | -t*42=3 | | 4a+12=4 | | -10m-8m=-24 | | 14/1+6/3 | | 1/2(6m-10)=3m-5 | | 27b+12b= | | 35=.2(255-10e) | | 3x+6=27+3 | | -1.1428x-6=-2.6x-14 | | (x+1)(x-1)(x-3)(x-6)=0 | | 6=-9-6 | | 51-7x=12+(-4x) | | 2x+3+5x=13 | | 5+3(n+9)=-3 | | 5+x-3[x+4]=-17 | | f(x)=2x+x-1 | | 3n-13=n+6 | | (x+5)(x-5)(x-7)=0 | | x^2+8x-7=8 | | 16x+18y+10x-7y= | | 5y^2+8y= | | 3k-2=39 | | 5X^3/(10x^2+5x) | | 5=-5+2x | | -x+3x-9=5 | | 9x+6-8=-38 |